The Role of AIK Education in Increasing Student Diversity Muhammadiyah University - Amin, Muh; Malik, Abdul (EDUKASIA, 2024)
This study explored the role of Al-Islam and Kemuhammadiyahan Education (PAIK) in shaping the students' character to be inclusive, tolerant, and integrity-driven within Muhammadiyah Higher Education institutions. Amid the increasing challenges of diversity and multiculturalism, the research highlighted the significance of PAIK in fostering leadership skills, social responsibility, and adaptability among students. Employing a qualitative research method with a library-based approach, this study comprehensively analyzed relevant literature, including books and academic journals, to draw meaningful insights. The findings revealed that PAIK significantly contributed to character development by integrating Islamic teachings and Muhammadiyah values into the students' academic and personal lives. It emphasized the cultivation of moral integrity, leadership qualities, and empathy towards societal dynamics. The study concluded that PAIK not only strengthened the students' religious foundation but also equipped them with essential competencies for navigating modern societal challenges. This research offered a novel perspective on Al-Islam and Muhammadiyah Curriculum (AIK) development and provided practical strategies for fostering diversity and tolerance in higher education, thus serving as a valuable reference for similar educational institutions seeking to achieve holistic student development.